Polyethylene Terephthalate (PET) Waste as Partial Aggregate and Reinforcement in Reinforced Concrete: A Review - Lingamen, Renz Brixter B.; Cruz, Orlean G. Dela (International Journal of Integrated Engineering, 2023)
Plastic disposal is now a significant problem for the sustainability of the environment. And, viewing the engineering properties of plastics (e.g., lightweight, flexible, strong, moisture-resistant, and cheap) opens the possibility of using them as a structural material. Over the decade, many researchers have studied using plastics as a replacement for natural aggregates in concrete or as an additive. Besides, past experimental results have shown that adding plastic waste in concrete will alter the concrete’s mechanical and durability properties. However, such concrete can still fulfill engineering properties and be used in other structures with low strength requirements. This research intends to try other possibilities of using plastic waste as partial aggregate and reinforcement in reinforced concrete. Therefore, it is proposed that researchers look into the effects of plastic particles in concrete on the environment and their durability over time due to its deterioration. It recommends surface treatment of plastics waste using appropriate chemicals.